THE PHARMACOKINETIC PARAMETERS DATA OF THE 20 MOST COMMONLY PRESCRIBED ANTIHYPERTENSIVE MEDICATIONS. (June 2022) - Alghamdi, Randah; Muhammad, Fahad; Osman, Hanad; Salim, Farah; Jenkins, Sian; Bernieh, Dennis; Gill, Henry; Lane, Dan; Squire, Iain; Jones, Donald; Gupta, Pankaj
Abstract : Objective: Chemical Adherence Testing (CAT) is now the preferred method for assessing adherence with prescribed medication. Further research is needed to understand the impact of pharmacokinetics(PK) on medication detection and adherence status, but there is no readily available collated literature. This study aims to collate PK data for 20 of the most prescribed antihypertensive medications. Design and method: Prescription rates were determined by reviewing CAT data of 3796 unselected hypertension patients whose samples were tested by the Department of Chemical Pathology & Metabolic Diseases, University Hospitals of Leicester NHS Trust. PK data of medications were obtained from published literature quoted from four sources: Goodman's & Gilman's: The Pharmacological Basis of Therapeutics 13th edition, Clarke's: Analysis of Drugs and Poisons 4th edition, Martindale: The Complete Drug Reference 39th edition and Micromedex: Medication database. All original manuscripts were reviewed and graded by applying robust criteria. Design and method: 228 articles were screened. A total of 99 articles were deemed suitable and subsequently had data extracted. The results showed the mean range of bioavailability for the 20 medications was 54.33 ± 27.53%, urine excretion 34.95 ± 28.07%, clearance 424.47 ± 745.75 ml/min/kg, the volume of distribution 169.85 ± 281.64L/kg, half-life 8.82 ± 6.53hrs, time to peak concentration 3.07 ± 2.08hrs and peak concentration 639.52 ± 1477.17ng/ml. The range of plasma concentrations was 1.96ng/ml for Moxonidine at the lowest concentration to 6400ng/ml for Valsartan at the highest concentration. Furosemide had the shortest half-life of 0.85hrs and, Amlodipine had the longest half-life of 59.6hrs. Amiloride was the maximum excretion of 87.9% in urine, whereas Spironolactone was the lowest excreted medication at 0.05%. Diltiazem's distribution volume was the highest at 822L/kg, whereas Furosemide had the lowest at 0.11L/kg. The medication clearance rate from the body ranged from 0.79 ml/min/kg for Valsartan to 2966 ml/min/kg for Diltiazem. Ramipril had the lowest bioavailability at 15%, while Bisoprolol and Indapamide at 90 % had the highest proportion of bioavailability. Results: This study is the first one that has collated PK parameters from published literature in a systematic manner for the most commonly prescribed antihypertensive medications. This will be of clinical use in providing interpretative information to clinicians when they review the results of CAT